Sherman, Clay County - Vincent, Albert (Kansas State University, The Chapman Center for Rural Studies, 2011)
Playing a major role in the railroad industry throughout the middle portion of the country, Sherman was a community inhabited by a wide range of ethnic groups. It saw a boom in economic activity but unfortunately, fell victim to a common die out of a town located too near the Republican River. Nevertheless, there was a time when Sherman was a lovely place to settle and live in.
Albert Vincent, “Sherman, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/70.
Keywords: Clay County; Sherman; Swedes; Germans; D. Seabury; Morganville